Measured effect of sexual activities, alcohol consumption, smoking and aggression on health risk of students in rural communities in Ikenne, Nigeria (2015)
This study examined the joint and relative contribution of sexual activities, alcohol consumption, smoking and aggression to the prediction of health risk of students in rural communities in Ogun State. Descriptive research design of correlational type was adopted. Multi-stage sampling Technique was used to draw 300 respondents from an approximated population size of 10,066 students. Two research questions guided the study. Thirty-nine item self-report questionnaire tagged “Health Risk Behaviours Questionnaire” was used for data collection. Result of Multivariate Analyses show that the predictor variables accounted for 38.9% of the variance in health risk of respondents (R= .657; R2= .389; F (3. 289) = 15.880; p <.05). Sexual activities made the most potent (β = .903) contribution to the prediction of health risk followed by alcohol consumption (β= .771), aggressive behaviours (β= .632) and smoking (β= .241). It concludes that the more students are involved in sexual activities, exhibits aggressive behaviours, consume alcohol and smoke the greater the likelihood that their health will be compromised. This outcome behooves counselling psychologists to design and implement health preventive, rehabilitative and reformatory counselling services for in-school adolescents